MUSYARAKAH FINANCE PROSPECT IN ISLAMIC BANK IN THE FACE OF ASEAN ECONOMIC COMMUNITY (MEA) - Supriyadi, Ahmad (ADDIN, 2016)
In the era of Dutch colonial, the majority of entrepreneurs in Central Java and Yogyakarta come from the students. But after Indonesian independence, the students did not show up in the business world because of political policy. Nowadays the entrepreneur students bounced back with Islamic banks that one of its products is a Musharakah finance. Musharakah finance deal with the birth of the free market, namely the ASEAN Economic Community so that the question arises how the prospect Musharakah finance in Indonesian Islamic banks of facing the ASEAN Economic Community (AEC). This paper aims to describe the prospect of Musharakah finance to face AEC. The results showed that the Musharakah finance has a lot of prospects such as financing products that can be performed well and have a competitive value because it has a solid legal basis. From the network side, Islamic banks have been supported by a network offices that much better at home and abroad with excellent quality customer service. In addition, the presence Bank Indonesia blueprint of the Islamic banking institution can strengthen the Musharakah finance products so that can be applied in the ASEAN Economic Community (AEC).